Risk Management in Offshore Wind Farm Development - ERIK, AHLGREN; Grudic, Edis (My University, 2017)
In addition to wind energy being a carbon dioxide and fossil free energy production, the main benefit with offshore construction as opposed to onshore is more frequent and stronger winds, which of course means a higher energy production. There are however also some disadvantages, building offshore is complex, cost intensive and is associated with more risks than onshore construction. The purpose of this thesis was to identify the major risks in offshore wind farm development and to unravel how those risks are controlled. Furthermore, the thesis aimed to investigate how the offshore wind farm industry is working with risk management and to provide suggestions for improvements by researching existing theories on risk management. Lastly, the Swedish offshore wind farm development as well as the potential risk reduction of building offshore wind farms in the Baltic Sea will be analyzed. To achieve the purpose, a case study on the offshore wind farm, Rødsand 2, was conducted where several of the actors involved in the project were interviewed regarding which risks they were exposed to and how those risks were controlled. The risk management plan used by E.ON for this particular project was analyzed and compared with existing theories on risk management. The results from the study shows that the major risks with offshore wind farm development is connected to weather and seabed condition. Furthermore, it is concluded that risk management is an area in offshore wind farm development which is taken very seriously and given a good amount of resources. The risk management plan as well as the risk management process used in Rødsand 2 follows a general approach to risk management and relevant tools and methods were used. There are however a few aspects which could be improved. The emphasization on positive risks needs to be given more resources, risk response plan should be considered in an earlier stage of the risk management process and the risk management plan should be more tailored to the industry it’s used in. Lastly, it’s concluded the building wind farms in the Baltic Sea is associated with less risk than building in, for example, the North Sea. Further research should focus on investigating the advantages and disadvantages of using a partnering contractual approach with cost-plus contracts between developers and subcontractors. This would mean a significant increase of the developer’s risk, but could have positive effects by lowering risk premiums, increasing quality and improving the transparency between client - contractors which could be beneficial in for example the risk identification phase.
Keywords: Samhällsbyggnadsteknik; Civil Engineering